A COMPARATIVE ANALYSIS OF PHONOLOGICAL ELEMENTS IN LAMPUNG LANGUAGE: DIALECT A PEMINGGIR AND DIALECT O ABUNG - Masitoh Masitoh; Meutia Rachmatia; Elis Susanti; Dewi Sri Kuning; Nabila Zatadini (University of Kuningan, 2023)
This study aims to investigate the differences in phonological elements between two dialects of the Lampung language: Dialect A Peminggir and Dialect O Abung. The research focuses on Lempasing Village, Padang Cermin District, Pesawaran Regency for Dialect A Peminggir, and Bumi Agung Marga Village, East Abung District, North Lampung Regency for Dialect O Abung. The objectives of this study are to describe: (1) the differences in vowel phonemes between Dialect A Peminggir and Dialect O Abung, (2) the differences in consonant phonemes between Dialect A Peminggir and Dialect O Abung, (3) the characteristics of diphthongs and vowel lines in Dialect A Peminggir and Dialect O Abung, (4) the differences in clusters and consonants between Dialect A Peminggir and Dialect O Abung, and (5) the variations in syllables between Dialect A Peminggir and Dialect O Abung. The study adopts a descriptive analytical method, and data collection involves the use of recording devices, tapes, and other stationery. The research utilizes various techniques, including listening or tapping techniques as basic methods, and advanced techniques such as free listening techniques, fishing techniques, recording techniques, questionnaires, and recording techniques. The results of the study demonstrate both differences and similarities in the phonological elements of Dialect A Peminggir and Dialect O Abung in the Lampung language.